Dynamic Regulation of Proteasome Expression - Motosugi, Ryo; Murata, Shigeo (Frontiers in Molecular Biosciences, 2019)
The 26S proteasome is a multisubunit complex that catalyzes the degradation of ubiquitinated proteins. The proteasome comprises 33 distinct subunits, all of which are essential for its function and structure. Proteasomes are necessary for various biological processes in cells; therefore, precise regulation of proteasome expression and activity is essential for maintaining cellular health and function. Two decades of research revealed that transcription factors such as Rpn4 and Nrf1 control expression of proteasomes. In this review, we focus on the current understanding and recent findings on the mechanisms underlying the regulation of proteasome expression, as well as the translational regulation of proteasomes.